FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS SAHAM SYARIAH INDONESIA (ISSI) DALAM JANGKA PANJANG DAN JANGKA PENDEK TAHUN 2019-2023 - Norlatifah Norlatifah; Sri Maulida (Diponegoro Journal of Islamic Economics and Business, 2025)
This study analyzes the factors influencing the Indonesia Sharia Stock Index (ISSI) in the long and short term during 2019–2023. The variables are grouped into internal factors (inflation, BI Rate, gold prices, and exchange rates) and external factors (The Fed interest rate, FTFBMHS, FTDQAS, and world oil prices). Using secondary data and the Vector Error Correction Model (VECM), the findings show that in the first model, inflation has a significant positive impact, while the BI Rate has a significant negative impact on ISSI in the long term. Exchange rates positively affect ISSI, while gold prices show no significant impact in either the long or short term. In the second model, FTFBMHS positively affects ISSI, whereas FTDQAS negatively influences ISSI in the long term. In the short term, The Fed interest rate and world oil prices exhibit a significant negative impact on ISSI.